RELASI MAKNA ANTARKALIMAT DALAM WACANA BERITA BBG NEWS - Harfiandi (Jurnal Metamorfosa, 2020)
This study is purposed to describe the meaning of inter sentences relation in the discourse context of BBG news. The data is derrived from the BBG news discourse sentences. It is a descriptive qualitative method that data collection was taken from BBG news documentation published in the June 2020 edition. The analysis procedures were started from data reduction, data presentation, and drawing conclusions. The main instrument of this study is the researcher itself that analyzes the data with referential matching techniques. Based on data analysis, it is found that there are relations between the meaning of anonymous, holonym, hypernim, hyponym, synonym, and antonym. In classifying data, it is done by sorting sentences to see the relationship of meaning. As determined, interalimatal relations are formed by processing intergral relationships from the totality of sentence information, the existence of hierarchical relationships above and below, relations of disagreement, and relations of equality in the formation of discourse in the news. Abstrak Tujuan penelitian ini mendeskripsikan hubungan makna antarkalimat dalam wacana BBG News. Data ini berupa kalimat dalam pembentukan wacana berita. Metode yang digunakan adalah deskriptif kualitatif. Pengumpulan data dilakukan dengan menggunakan teknik dokumentasi berita yang terbit pada edisi bulan Juni 2020. Analisis yang dilakukan dengan reduksi data, penyajian data, dan penarikan kesimpulan. Instrumen penelitian ini adalah peneliti yang melakukan analisis terhadap data dengan teknik padan referensial. Berdasarkan analisis data, terdapat jenis relasi makna meronim, holonim, hipernim, hiponim, sinonim, dan antonim. Dalam penglasifikasian data, dilakukan dengan pengurutan kalimat untuk melihat hubungan makna. Sebagaimana yang ditentukan, hubungan antarkalimat terbentuk dengan pengolahan hubungan intergral dari kesuluruhan informasi kalimat, adanya hubungan hierarki atas bawah, hubungan pertentangan, dan hubungan persamaan dalam pembentukan wacana dalam berita. Kata Kunci: Relasi Makna, Antarkalimat, Pembentukan Wacana, Berita BBG